Penyusunan Laporan Keuangan Berdasarkan SAK-EMKM Pada Umkm Warung Makan Mbak Rina - Nurfadilah Ukhti Fatahillah (UMSurabaya Publishing, 2021)
The purpose of this research found out how to prepare financial statements based on SAK-EMKM at Mbak Rina’s Food Stall. The type of research used descriptive qualitative. The data used primary data that obtained from interviews with MSME owner and data in the form of cash diaries. While secondary data obtained from journals, books, and the internet. The results showed that: (1) The owner of the Mbak Rina’s Food Stall did not know the need to prepare financial statements, because they did not have previous financial reports. (2) The owner of the Mbak Rina’s Food Stall did not understand the purpose of the preparation of financial statements, the owner only applied the recording of cash in and cash out. The financial statements prepared by the researcher were the Income Statement, Statement of Financial Position, and Notes to Financial Statements. Mbak Rina’s Food Stall did not yet have a tax burden. Therefore, the net profit value was not deducted by the tax burden.